2016
DOI: 10.7150/jca.14120
|View full text |Cite
|
Sign up to set email alerts
|

Vasculogenic Mimicry in Prostate Cancer: The Roles of EphA2 and PI3K

Abstract: BACKGROUND. Aggressive tumor cells can form perfusable networks that mimic normal vasculature and enhance tumor growth and metastasis. A number of molecular players have been implicated in such vasculogenic mimicry, among them the receptor tyrosine kinase EphA2, which is aberrantly expressed in aggressive tumors. Here we study the role and regulation of EphA2 in vasculogenic mimicry in prostate cancer where this phenomenon is still poorly understood.METHODS. Vasculogenic mimicry was characterized by tubules wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 32 publications
7
42
0
Order By: Relevance
“…In addition, VM is found in many solid tumors, including but not limited to the cancer mentioned above: Melanoma, hepatocellular carcinoma, colorectal and prostate cancer (4,6,8,10). Furthermore, there is a strong correlation between VM and malignant features of cancer, such as advanced stage or grade, poor differentiation and short overall survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, VM is found in many solid tumors, including but not limited to the cancer mentioned above: Melanoma, hepatocellular carcinoma, colorectal and prostate cancer (4,6,8,10). Furthermore, there is a strong correlation between VM and malignant features of cancer, such as advanced stage or grade, poor differentiation and short overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon has been observed in many tumor types, including hepatocellular carcinoma, breast, colorectal and prostate cancer (5)(6)(7)(8). Numerous studies (8)(9)(10) have shown that the existence of VM is closely related to the invasion, metastasis and poor prognosis of malignant tumors, which is significant in the clinic. At present, the literature about VM in bladder cancer, particularly its molecular mechanism, is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…The Src inhibitor PP2 was purchased from MedChemExpress (Trenton, NJ, USA) and dissolved in dimethyl sulfoxide (DMSO) and then used to treat cells at concentrations between 0 and 20 μmol/L, while cells treated with DMSO alone were used as controls …”
Section: Methodsmentioning
confidence: 99%
“…This assay was performed to assess the capacity of tumour cells to form VM as described previously . Briefly, we first coated 96‐well plates with growth factor‐reduced Matrigel (BD Biosciences, Bedford, MA) at 50 μL/well.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation